2022
DOI: 10.3390/environments9040043
|View full text |Cite
|
Sign up to set email alerts
|

Groundwater Hydrogeochemical and Quality Appraisal for Agriculture Irrigation in Greenbelt Area, Iraq

Abstract: This study highlights the groundwater hydrogeochemical characteristics and processes (hydrochemistry characteristics, ion exchange, and salinization) and quality suitability assessment for irrigation purposes from five wells in the Greenbelt area located in northwestern Al-Najaf Governorate, Iraq. The suitability of groundwater for irrigation was assessed based on the irrigation water quality index (IWQI) for thirteen parameters and groundwater quality indices such as total dissolved solids (TDS), electrical c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Photocatalysts are the heart of photocatalytic technology, which has gained popularity as a green method for the total degradation of organic pollutants utilizing a freely available solar energy source without emitting any secondary pollution (Wen et al 2020;Bai et al 2021). Today, various sciences (Alimadadi et al 2019;Volodymyr et al 2021;Akter et al 2022) such as environment (Alshehrei et al 2021;Wang et al 2021a;Awad et al 2022;Dai et al 2022a), engineering (Assi et al 2021;Hussein et al 2021;Li et al 2021a;Majdi & Vacareanu 2021), computer (Liu et al 2021b), agriculture (Tian et al 2021a(Tian et al , 2021bWang et al 2022a), chemistry (Ge et al 2019;Liu et al 2020;Qin et al 2022), physics (Li et al 2022a), and medicine (Chen & Wang 2021;Endriani et al 2022;Kausikan et al 2022;Mahawar et al 2022;Zheng et al 2022) have made significant progress (Amiri et al 2020;Chu et al 2020;Zhao et al 2020aZhao et al , 2021aZhao et al , 2021bZhao et al , 2021cZhao et al , 2021dNazeer et al 2022;Rashid et al 2022a;Zhao et al 2022aZhao et al , 2022b. Nanoscience is no exception to this rule (Barani et al 2020;Bilal et al 2020;…”
Section: Introductionmentioning
confidence: 99%
“…Photocatalysts are the heart of photocatalytic technology, which has gained popularity as a green method for the total degradation of organic pollutants utilizing a freely available solar energy source without emitting any secondary pollution (Wen et al 2020;Bai et al 2021). Today, various sciences (Alimadadi et al 2019;Volodymyr et al 2021;Akter et al 2022) such as environment (Alshehrei et al 2021;Wang et al 2021a;Awad et al 2022;Dai et al 2022a), engineering (Assi et al 2021;Hussein et al 2021;Li et al 2021a;Majdi & Vacareanu 2021), computer (Liu et al 2021b), agriculture (Tian et al 2021a(Tian et al , 2021bWang et al 2022a), chemistry (Ge et al 2019;Liu et al 2020;Qin et al 2022), physics (Li et al 2022a), and medicine (Chen & Wang 2021;Endriani et al 2022;Kausikan et al 2022;Mahawar et al 2022;Zheng et al 2022) have made significant progress (Amiri et al 2020;Chu et al 2020;Zhao et al 2020aZhao et al , 2021aZhao et al , 2021bZhao et al , 2021cZhao et al , 2021dNazeer et al 2022;Rashid et al 2022a;Zhao et al 2022aZhao et al , 2022b. Nanoscience is no exception to this rule (Barani et al 2020;Bilal et al 2020;…”
Section: Introductionmentioning
confidence: 99%
“…Nanotechnology is a new and rapidly growing field of science (AlNadhari et al, 2021; Bai, Nie, et al, 2021; Huseien et al, 2022; Li, Sun, & Wu, 2022; Xin et al, 2021; Yang, Li, Luo, et al, 2021). Nanotechnology contribute in diverse field of science such as chemistry (Assi et al, 2021; Chu et al, 2021; Gao et al, 2019; Gao et al, 2021; Jia et al, 2022; Wang et al, 2022), materials (Bai, Jiang, et al, 2021; Chu et al, 2022; Guo et al, 2017; Min et al, 2019; Yang et al, 2017), health (Yan et al, 2020; Yang, Li, Said, et al, 2021), food safety (Ameen & Al‐Homaidan, 2022; Hu et al, 2021; Liu, Li, Cao, et al, 2021; Ngafwan et al, 2021), separation (ANZUM et al, 2022; Majdi & Vacareanu, 2021), agriculture (Awad et al, 2022; Gunawan et al, 2022; Li et al, 2016; Liu, Li, Zhang, et al, 2021; Wang et al, 2018; Wang, Li, et al, 2020; Zhang et al, 2022), drug delivery (Lai et al, 2020; Lai et al, 2021), sensor (Chupradit et al, 2022; Chupradit, Ashfaq, et al, 2021; Indhira et al, 2022; Liu, Zheng, Wang, et al, 2021; Yumashev et al, 2022), and computer science (Chu, Wang, & Zhao, 2014; Chu & Zhao, 2016; Hanan et al, 2021; Hussein et al, 2021; Kadri et al, 2022; Karthikeyan et al, 2021; Zhao et al, 2018; Zhao, Wang, & Chu, 2020). Innovations in the existing nano‐pharmaceutical formulations are increasing, and the production of nanoparticles (NPs) with varying sizes, shapes, distributions, and controlled shapes are new challenges in these studies (Jasim, Patra, et al, 2022; Li et al, 2013; Sadeghi, Alijani, et...…”
Section: Introductionmentioning
confidence: 99%
“…Several types of nanostructures(Darvish et al, 2022;Hu et al, 2022) have shown significant antimicrobial activity against antibiotic-resistant and even multidrugresistant strains(Alshehrei et al, 2021;Bala Subramaniyan et al, 2022;Jampilek & Kralova, 2022).Nanotechnology is a new and rapidly growing field of science(AlNadhari et al, 2021;Bai, Nie, et al, 2021;Huseien et al, 2022;Xin et al, 2021;Yang, Li, Luo, et al, 2021). Nanotechnology contribute in diverse field of science such as chemistry(Assi et al, 2021;Chu et al, 2021;Gao et al, 2019;Gao et al, 2021;Jia et al, 2022;Wang et al, 2022), materials(Bai, Jiang, et al, 2021;Chu et al, 2022;Guo et al, 2017;Min et al, 2019;Yang et al, 2017), health(Yan et al, 2020;Yang, Li, Said, et al, 2021), food safety(Ameen & Al-Homaidan, 2022;Hu et al, 2021;Ngafwan et al, 2021), separation(ANZUM et al, 2022;, agriculture(Awad et al, 2022;Gunawan et al, 2022;Li et al, 2016;Wang et al, 2018;Wang, Li, et al, 2020;Zhang et al, 2022), drug delivery(Lai et al, 2020;Lai et al, 2021), sensor(Chupradit et al, 2022;Chupradit, Ashfaq, et al, 2021;Indhira et al, 2022;Liu, Zheng, Wang, et al, 2021;Yumashev et al, 2022), and co...…”
mentioning
confidence: 99%
“…The energy consumption in this method is much less than chemical methods, and due to the compatibility with the environment, it is necessary to develop green methods [68]. New developments in science [69][70][71][72][73][74][75] and technology [76] have significant impact on human health [77][78][79][80][81] and life [82,83].…”
Section: Introductionmentioning
confidence: 99%